Intimate partner violence - Hattery, Angela (Rowman & Littlefield, 2009)
Setting the stage -- Individual factors that contribute to IPV -- Structural supports for intimate partner violence : capitalism, racism, and patriarchy -- Cultural supports for intimate partner violence : constructions of masculinity and femininity -- Race and intimate partner violence : violence in interracial and intraracial relationships -- We were made for each other : definitions of romantic love and ties to interpersonal violence -- Where do we go from here? The search for equality